Castles, Stephen y Mark J. Miller. The age of migration : international population movements in the modern world. Nueva York : The Guilford Press, 1998 - Giorguli Saucedo, Silvia Elena (Estudios Demográficos y Urbanos, 2002)
Castles, Stephen y Mark J. Miller, The Age of Migration. International Population Movements in the Modern World, Nueva York, The Guilford Press, 1998.